x^2 + y^2 + 2x - 6y - 6 = 0
We're inevitably going to complete the square, so the first thing we need to do is rearrange the terms so that the x terms are together and the y terms are together.
x^2 + 2x + y^2 - 6y - 6 = 0
We need to complete the square with the x terms, and complete the square with the y terms. We look at the coefficient of x (which is 2), and the coefficient of y (which is -6), and add "half squared" of each of those terms. Half squared of 2 is 1, and half squared of -6 is 9, so we add 1 and 9 to both sides.
x^2 + 2x + 1 + y^2 - 6y + 9 - 6 = 1 + 9
Change into binomial squares,
(x + 1)^2 + (y - 3)^2 + - 6 = 10
(x + 1)^2 + (y - 3)^2 = 16
Edit: Thanks for pointing out the correct to the answerers below.
2007-01-19 04:57:41
·
answer #1
·
answered by Puggy 7
·
0⤊
1⤋
The standard form for the circle is (x - a)^2 + (y - b)^2 = r^2, where the center is (a,b) and the radius is r. You want to put x^2 + y^2 + 2x - 6y - 6 = 0 into this form.
Group the x terms together. Do the same with the y terms. Move the rest to the other side:
x^2 + y^2 + 2x - 6y - 6 = 0
(x^2 + 2x) + (y^2 - 6y) = 6
Now use completing-the-square on each group on the left, so that you can get the first group into the form of (x-a)^2 and the second into the form of (y-b)^2. You should end up with "1" having to be added to the first group, and "9" being added to the second group in order to complete the squares:
(x^2 + 2x + 1 -1) + (y^2 - 6y + 9-9) = 6
(x^2 + 2x + 1) -1 + (y^2 - 6y + 9) -9 = 6
(x+1)^2 - 1 + (y - 3)^2 - 9 = 6
(x+1)^2 + (y - 3)^2 = 16
(x+1)^2 + (y - 3)^2 = 4^2
2007-01-19 05:06:41
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
Complete the squares!
x² + y² + 2x - 6y - 6 = 0
â (x² + 2x + 1) + (y² - 6y + 9) = 16
â (x+1)² + (y-3)² = 16.
Radius 4, centered at (-1,3).
2007-01-19 04:59:50
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Puggy, I don't know how you mis-subtracted after that brilliant answer, but the RHS should equal 16 when all is said & done.
2007-01-19 05:00:13
·
answer #4
·
answered by bequalming 5
·
0⤊
0⤋